2017
DOI: 10.1039/c7nr02554h
|View full text |Cite
|
Sign up to set email alerts
|

Charge storage performances and mechanisms of MnO2 nanospheres, nanorods, nanotubes and nanosheets

Abstract: Manganese dioxide (MnO) has been widely used as an active material for high-performance supercapacitors due to its high theoretical capacitance, high cycling stability, low cost, and environmental friendliness. However, the effect of its crystallographic phase on charge storage performances and mechanisms is not yet clear. Herein, MnO-based supercapacitors with different structures including nanospheres, nanorods, nanotubes, and nanosheets have been fabricated and investigated. Among such structures, δ-MnO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 77 publications
3
57
0
1
Order By: Relevance
“…However, EDLCs always show much lower specic capacitance and energy density than PCs owing to the fact that EDLCs mainly rely on the charge storage on the interface between the electrode material and the electrolyte ions. [9][10][11] However, PCs depend on the rapid and reversible faradaic reactions that occur on the surface of the electrode material. 12,13 The key to pseudocapacitors is the preparation of electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, EDLCs always show much lower specic capacitance and energy density than PCs owing to the fact that EDLCs mainly rely on the charge storage on the interface between the electrode material and the electrolyte ions. [9][10][11] However, PCs depend on the rapid and reversible faradaic reactions that occur on the surface of the electrode material. 12,13 The key to pseudocapacitors is the preparation of electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology also has an impact on how charges are stored by MnO x ‐based electrodes. In Sawangphruk's work, for example, it was found that for MnO 2 nanosheets, diffusion was the dominant process during charge storage; while for MnO 2 nanospheres, nanorods, and nanotubes, charge was stored by both diffusion and nondiffusion controlled processes. The morphology of a specific MnO x nanomaterial can be tuned through facet engineering .…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors are classified into electric double layer capacitors (EDLC) where the charges are stored electrostatically through separation of charges and pseudocapacitors (PC) where the charges are stored faradaically involving electrochemical redox reaction, electrosorption and intercalation of ions or atoms between electrode and electrolyte [12,13]. Faradaic storage mechanism of charge makes pesudocapacitors meritorious by giving higher energy density than EDLC [14][15][16]. Transition metal oxide is considered as an ideal pesudocapacitor electrode material attributing to their intrinsically high pseudocapacitive behaviour of fast and reversible surface redox reactions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%